The causes of stress on intestinal microbiota of Atlantic salmon, Arctic charr, Atlantic cod and rainbow trout - Xafri, Monjurul; Arafat, Chakra; Farzana, Saminul (Advances in Aquaculture and Fisheries Management, 2013)
The gastrointestinal (GI) tract of fish reacts to stress, sometimes with severe cell damage to intestinal enterocytes and modulation of the gut bacterial community. The effect of dominance hierarchy formation, acute - and handling stress on the intestinal bacterial community have been reported in three salmonids; Arctic charr (Salvelinus alpinus L.), Atlantic salmon (Salmo salar L.) and rainbow trout (Oncorhynchus mykiss Walbaum), and Atlantic cod (Gadus morhua L.). In Arctic charr, hierarchy formation reduced cultivable autochthonous (adherent) bacteria level in proximal intestine of subordinate fish compared to dominant fish, but this effect was not noticed in the distal intestine (DI). Furthermore, hierarchy formation modulates the gut microbiota. When Atlantic salmon and rainbow trout were exposed to acute stress the population level of adherent bacteria decrease in DI with concomitant increase in faeces, but this effect was not observed in Atlantic cod. The reason for the effect in Atlantic salmon is probably a peel-off effect of mucus and transporting autochthonous gut bacteria out of the fish. This will in turn allow allochthonous bacteria (present in the lumen or associated to digesta) to adhere and colonise the mucus layer. The elimination of the existing beneficial adherent gut microbiota and the lack of protecting mucus during acute stress might have relevance in pathogenesis. The present study reveals that stress eliminates certain protecting bacteria in the GI tract making the gut more prone to pathogen infections.